2009
DOI: 10.1002/btpr.226
|View full text |Cite
|
Sign up to set email alerts
|

Progress technology in microencapsulation methods for cell therapy

Abstract: Cell encapsulation in microcapsules allows the in situ delivery of secreted proteins to treat different pathological conditions. Spherical microcapsules offer optimal surface-to-volume ratio for protein and nutrient diffusion, and thus, cell viability. This technology permits cell survival along with protein secretion activity upon appropriate host stimuli without the deleterious effects of immunosuppressant drugs. Microcapsules can be classified in 3 categories: matrix-core/shell microcapsules, liquid-core/sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 182 publications
(192 reference statements)
1
93
0
1
Order By: Relevance
“…Thus, the process of particle formation has to be carefully selected. Droplet production can essentially be classified in to two types: single or series drop formation techniques (extrusion-laminar jet break-up [15]; microfluidic devices [21]), and bulk or parallel techniques (stirring [7,36]; Membrane Emulsification (ME) [20])). To-date, Song et al [20] is the only work reported for the encapsulation of cells using an SPG membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the process of particle formation has to be carefully selected. Droplet production can essentially be classified in to two types: single or series drop formation techniques (extrusion-laminar jet break-up [15]; microfluidic devices [21]), and bulk or parallel techniques (stirring [7,36]; Membrane Emulsification (ME) [20])). To-date, Song et al [20] is the only work reported for the encapsulation of cells using an SPG membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Among these technologies are PEGylation (22), layer-by-layer (23)(24)(25)(26)(27), and conformal coating (28)(29)(30)(31)(32), which are based on chemically reacting hydrogels directly to the cell surface (21,33,34), as well as the development of ALG derivatives with enhanced performance (35). Although successful in vitro, most technologies have not achieved success as immune barriers in preclinical and clinical models, still requiring systemic immunosuppression (36).…”
mentioning
confidence: 99%
“…the immobilization of cells within polymeric microspheres or microcapsules, has permitted the transplantation of cells into human and animal subjects without the need for immunosuppressants, while allowing the bidirectional diffusion of nutrients, oxygen and waste (Murua et al, 2008). Microencapsulation materials have comprised natural or synthetic polymers or blends, including alginate, collagen, gelatin, fibrin, polyphosphazenes, poly(acrylic acids), poly(methacrylic acids), copolymers of acrylic acid and methacrylic acid, poly(alkylene oxides), poly(vinyl acetate), polyvinylpyrrolidone, PEG, polyethersulfone, polysaccharides such as agarose, cellulose sulfate, chondroitin sulfate, chitosan, hyaluronan, and copolymers, and blends of each (Rabanel et al, 2009). The first implantable alginatepoly(L-lysine) microcapsules for the treatment of diabetes were presented by Lim and Sun, (1980).…”
Section: Cell Encapsulationmentioning
confidence: 99%